Identifying Engaged Couples’ Knowledge and Attitudes about Family Planning - POTUR, DİLEK (My University, 2019)
Objective: This study was conducted to identify engagedcouples’ knowledge and attitudes about family planning.Method: This cross-sectional and descriptive study wasconducted with 195 engaged couples between July 2013and June 2014 at a province in Northern Turkey.“Participant Identification Form” and “Family PlanningAttitude Scale” were used for data collection.Results: Less than half of the participating engaged couples (female: 42.6%, male: 38.5%), received informationabout family planning methods. Males knew fewer(3.91±2.73) contraceptive methods than females(4.57±2.95). The method mostly known to females was thebirth control pill whereas males were most familiar withcondoms. As compared to males, females had a more positive attitude towards family planning (p<0.05). The characteristics that were identified as affecting engagedpeople’s attitudes towards family planning included education level, satisfaction with their existing family planningknowledge, and intention to use contraceptive methodsafter marriage (p<0.05).Conclusion: Engaged couples generally have positive attitudes towards family planning. Women have a more positive attitude towards family planning than males.

Amaç: Bu çalışma nişanlı çiftlerin aile planlamasına ilişkin bilgi ve tutumlarını belirlemek için yapılmıştır. Yöntem: Tanımlayıcı ve kesitsel tipteki çalışma, Temmuz 2013 ve Haziran 2014 tarihleri arasında Türkiye’nin kuzeyinde yer alan bir ilde, 195 nişanlı çift ile yapılmıştır. Verilerin toplanmasında “Katılımcı Bilgi Formu” ve “Aile Planlaması Tutum Ölçeği” kullanılmıştır. Bulgular: Çalışmaya katılan nişanlı çiftlerin yarıdan azı (kadın: %42,6, erkek %38,5) aile planlaması yöntemleri hakkında bilgi sahibidir. Erkeklerin bildiği aile planlaması yöntem sayısı (3,91±2,73), kadınların bildiği yöntem sayısından (4,57±2,95) daha azdır. Kadınlar tarafından en fazla bilinen yöntem oral kontraseptif, erkeklerde kondomdur. Kadınlar erkeklere göre aile planlamasına yönelik daha olumlu tutuma sahiptirler (p<0,05). Nişanlı çiftlerin eğitim düzeyi, alınan aile planlaması bilgisini yeterli bulma, evlendikten sonra yöntem kullanmayı düşünme gibi özelliklerinin aile planlaması tutumunu etkilediği belirlenmiştir (p<0,05). Sonuç: Nişanlı çiftler genel olarak aile planlamasına yönelik olumlu tutuma sahip olup, kadınların erkeklere göre aile planlaması tutumları daha olumludur.
Nişanlı Çiftlerin Aile Planlamasına İlişkin Bilgi ve Tutumlarının Belirlenmesi
Keywords: Sağlık Bilimleri ve Hizmetleri; Sağlık Politikaları ve Hizmetleri; Hemşirelik